Targeting Resistance Pathways in Breast Cancer Through Precision Oncology: Nanotechnology and Immune Modulation Approaches - Hussein Sabit; Sanaa Rashwan; Yasser Albrahim; Al-Hassan Soliman Wadan; Faisal Radwan; Amany I. Alqosaibi; Shaimaa Abdel-Ghany; Borros Arneth (Biomedicines)
According to the WHO, in 2022, there were 2.3 million women diagnosed with breast cancer (BC) and 670,000 deaths globally. BC remains the leading cause of cancer-related mortality, with therapeutic resistance representing a significant barrier to effective treatment, particularly in aggressive subtypes like triple-negative breast cancer (TNBC). This review article discusses emerging strategies to overcome resistance by integrating precision oncology, nanotechnology-based drug delivery, and immune modulation. Resistance mechanisms—such as metabolic reprogramming, tumor heterogeneity, immune evasion, autophagy, and the role of cancer stem cells—are critically examined. We highlight cutting-edge nanoplatforms that co-deliver chemotherapeutics and immune stimulants with spatiotemporal precision, including sonodynamic and photothermal systems, ADCs, and targeted nanoparticles. Moreover, advances in tumor microenvironment (TME) modulation, photoimmunotherapy, and exosomal miRNA targeting offer promising avenues to enhance immunogenicity and therapeutic durability. The integration of molecular profiling with advanced computational approaches, including artificial intelligence and biomimetic models, holds significant promise for the future development of personalized resistance-mitigating interventions, though a detailed exploration is beyond the current scope. Collectively, these strategies reflect a paradigm shift from conventional monotherapies toward multifaceted, precision-guided treatment approaches. This review aims to provide a comprehensive overview of current innovations and propose future directions for overcoming drug resistance in BC.